INFLUENCE OF ONLINE SALES PROMOTION ON PURCHASE DECISIONS OF CORK FISH (Channa striata) SEMPOL SUBSTITUTION OF CORK FISH BONE FLOUR AS A SOURCE OF CALCIUM FOR THE PREVENTION OF OSTEOPOROSIS IN WOMEN - Anggraeni, Nabila; Pudjirahaju, Astutik (Jurnal Pendidikan Kesehatan, 2025)
There is a relationship between calcium intake and bone density in postmenopausal women (Hayati, S. and Herwana, E., 2018). Sales promotion has an effect on increasing sales in motorcycle companies (Togoldy, E., et al, 2018). Analyze online sales promotion, analyze buying decisions, and analyze the effect of online sales promotion on the decision to buy cork fish sempol. Type of research ex post facto cross sectional design. The population of this study were women who saw advertisements for sempol ikan gabus products. Target promotion 30 women aged 16 - 29 years. Most respondents (45.5%) rated the price of sempol products as very good, price affordability as very good (54.5%), access to information on sempol products as very good (52.3%), product advertisements as very good (50.0%), advertising information on sempol products as very good (47.7%), the number of respondents who saw advertisement as very good (61.4%). Most respondents (61.4%) gave a very good assessment that respondents buy products according to their wishes and according to their needs (43.2%), product quality is very good (56.8%), the match with consumer expectations is very good (52.3%), it is very good that they will make repeat purchases (56.8%), and recommend products to friends (59.1%). Respondents who rate online sales promotions very well get a high product purchase decision value and vice versa. There is a relationship between sales promotion and the decision to buy cork fish sempol.